DEVELOPING EFL LEARNERS’ ACHIEVEMENT COMMUNICATION STRATEGIES IN A SPEAKING CLASS (Jurnal Tatsqif, 2016)
Communication strategies should be included in a speaking class in order to enable learners have strategies to cope with the communication problems both as message delivers (speakers) and as message receivers (listeners) in taking turns speaking. When the learners face problems in taking turns speaking, they may employ achievement/compensatory strategies as an attempt to deal with problems in communication directly by using alternative in order to get the message across. The use these strategies are regarded as good learners’ behaviors because they are able to maintain communication, such as use of word coinage, language switch, paraphrase, circumlocution, cooperative strategies, non-linguistic strategies, and so forth. Otherwise, the learners may rely on the avoidance/reduction strategies if they are not able to convey or understand the message to or from the interlocutors. These behaviors affect interaction negatively and are common among low proficiency learners. The avoidance message as such topic avoidance, message abandonment, replace the message, reduce the content of the intended message, and so forth. Learners as message delivers (speakers) and message receivers (listeners) may use verbal communication strategies to cope with communication problems, such as topic avoidance, message abandonment, approximation, word coinage, circumlocution, literal translation (interlingual transfer), language switch, appeal for assistance, foreignizing (interlingual transfer), paraphrase, self-correction, self-repetition, asking for repetition, asking for clarification, and so forth. Meanwhile, nonverbal CSs which may be employed by learners as message senders (speakers) and message receivers (listeners) are smiling, head nodding, head shaking, hand raising, hand moving, thumb up, drawing something, and so forth.